An exploration of the factors which predict the quality of the mentoring experience in beyond registration healthcare learning. (16th August 2010) - Norrie, Peter; Lewis, Deborah; Parboteeah, Sam; Greenway, Carol
Mentoring is widely used to support learning within healthcare settings. It is an essential component of a range of Learning Beyond Registration programmes in the UK. This research project used an extensive literature review to identify the variables reported as affecting student experiences of mentoring quality. In addition to producing descriptive data, multiple regressions were used to produce a parsimonious model which explained the descriptive findings. Four items were found to account for 59% of the variance. These can be summarised as the mentor: 1) not being pressured and having time to give quality supervision; 2) being committed to the mentoring relationship; 3) being non-judgemental; 4) giving emotional support. It is suggested that a process of matching between mentors and students could enhance these positive traits and that these findings may contribute to mentoring models.